Simulation and modeling for controlling stepper motor with tuned PID by GWO: comparative study - Shneen, Salam Waley; Dakheel, Hashmia S.; Abdullah, Zainab B. (Institute of Advanced Engineering and Science, 2024)
The current work aims to simulate the operation of the electric motor in one of the most important industrial applications, which is printers, by adopting stepper motors (SM). The performance of the motor is also improved by adopting traditional control systems and adjusting them using the gray wolf optimization (GWO) advanced algorithm. It works to adjust the parameters of a conventional controller. Simulation to reach an appropriate design with high performance, which is obtained by adopting the integral time absolute error (ITAE) function to get rid of the error for transient cases. Transfer function was adopted to represent the engine and two methods of control were used, traditional and advanced optimization. Results demonstrated the possibility of improving performance by adopting both methods with a clear superiority of advanced optimization. Response of SM without controller for close loop shows the values of each rising time equal 130.440 ms, overshoot equal 0.505%, and undershoot equal 1.077%. Response of SM for close loop with proportional-integral-derivative controllers (PIDC) shows the parameters, performance, and robustness of PIDC also the values of overshoot=9.16%, settling time=0.406, and rise time=0.0628 s. Results were developed by using GWO-PID over the previous cases by reducing values of overshoot to zero, rise time, and settling time to 0.00145 and 0.0027 respectively.